Trends in sociodemographic and lifestyle factors associated with sedentary behavior among Brazilian adults - Trindade , Lucas Akio Iza (2020)
Objective: To analyze sociodemographic and lifestyle factors associated with screen-based sedentary behavior (watching television ≥3 hours/day) among adult individuals in Brazil. Methods: Quantitative analysis of ten editions of the cross-sectional health survey VIGITEL, representative at population level. Individuals from states’ capitals living in households with land-line telephone were randomly selected and interviewed using structured questionnaire by telephone. A multivariate logistic regression model was estimated for identification of factors associated with screen-based sedentary behavior. Results: There was stability in trends referring to prevalence of sedentary behavior from 2008 to 2017. Prevalence of sedentary behavior was higher between individuals with unhealthier lifestyles: consumption of <2 in natura food items (vegetables, fruits and beans) per day (26.73% [95%CI 25.2%;28.31%]) in comparison to ≥2 items per day (23.79% [95%CI 21.92%;25.77%]); consumption of soft drinks ≥5 days per week (31.24% [95%CI 29.58%;32.95%]) than <5 days per week (23.82% [95%CI 22.2%;25.52%]); and practice of <150 minutes of physical activity per week (28.2% [95%CI 26.17%;30.33%]) than ≥150 minutes per week (22.54% [21.27%;23.86%]). Regular consumption of in natura food items (OR=0.984), practice of physical activity (OR=0.798) and living in richer municipality (OR=0.826) represented protective factors in relation to screen-based sedentary behavior, whilst regular consumption of soft drinks (OR=1.440), smoking (OR=1.375) and alcohol abuse (OR=1.334) represented risk factors. Conclusion: The adoption of screen-based sedentary behavior among adult individuals in Brazil presented significant association with modifiable behavioral factors in the period 2008-2017.